Evaluation of commercial traits in the accessions of the wheatgrass genus (Agropyron Gaertn.) under the conditions of Central Yakutia - A. A. Kochegina; V. M. Koryakina (Труды по прикладной ботанике, генетике и селекции)
Studying plants of the wheatgrass genus as a unique and valuable fodder and phytomeliorating perennial arid xerophytic crop is of great interest to plant breeders, geneticists, biologists, ecologists, agriculturists, and forestry experts in southern regions of Russia, the ex-USSR republics, a number of European and Asia Minor countries, the U. S., Canada, and China. Accessions from the VIR collection representing five wheatgrass species were studied for the first time under the harsh conditions of extremely continental climate in the northern region of Central Yakutia. Introducing wheatgrass, widespread in this region, into cultivation, and releasing new cultivars adapted to local conditions are urgent tasks in forage production. Agropyron Gaertn. incorporates polyploid series, which expands the possibilities of using its accessions in hybridization.   The aim of this study was to analyze and select promising accessions as sources for further use in breeding practice to develop a new cultivar for hay and pasture purposes, and identify genotypes with the best agronomic characteristics.   Results of a three-year (2018–2020) study involving 22 wheatgrass accessions of various ecogeographic origin are presented. The accessions identified over a two-year period for their average yield of green fodder biomass were k-52382 (143.7 g/plant) from Pavlodar Region of Kazakhstan, and the Kazakh cultivar ‘Batyr’ (142.5 g/plant); for the yield of dry fodder biomass, crested wheatgrass k-52382 (on average 65.8 g/plant), k-51330 from Chelyabinsk Province (56.1 g/plant), and cv. ‘Batyr’ (53.2 g/plant); for high seed yield, Siberian wheatgrass accession k-52440 (28.4 g/m2), wild crested wheatgrass k-51330 (25.2 g/m2) and k-52380 (19.4 g/m2), and Kerch wheatgrass k-48705 (17.3 g/m2). Nutrients and energy in the tested accessions were assessed.